PPP3CA truncating variants clustered in the regulatory domain cause early‐onset refractory epilepsy. Issue 2 (1st June 2021) - Panneerselvam, Sugi; Wang, Julia; Zhu, Wenmiao; Dai, Hongzheng; Pappas, John G.; Rabin, Rachel; Low, Karen J.; Rosenfeld, Jill A.; Emrick, Lisa; Xiao, Rui; Xia, Fan; Yang, Yaping; et al.
Abstract: PPP3CA encodes the catalytic subunit of calcineurin, a calcium‐calmodulin‐regulated serine–threonine phosphatase. Loss‐of‐function (LoF) variants in the catalytic domain have been associated with epilepsy, while gain‐of‐function (GoF) variants in the auto‐inhibitory domain cause multiple congenital abnormalities. We herein report five new patients with de novo PPP3CA variants. Interestingly, the two frameshift variants in this study and the six truncating variants reported previously are all located within a 26‐amino acid region in the regulatory domain (RD). Patients with a truncating variant had more severe earlier onset seizures compared to patients with a LoF missense variant, while autism spectrum disorder was a more frequent feature in the latter. Expression studies of a truncating variant showed apparent RNA expression from the mutant allele, but no detectable mutant protein. Our data suggest that PPP3CA truncating variants clustered in the RD, causing more severe early‐onset refractory epilepsy and representing a type of variants distinct from LoF or GoF missense variants. Abstract : We provided molecular and clinical findings of five new patients with de novo PPP3CA variants. Interestingly, the two frameshift variants in this study and the six truncating variants previously reported are all clustered within a small 26‐amino acid region in the regulatory domain (RD). Genotype‐phenotype correlation of the 21 patients with PPP3CA mutations and expression studies on truncating mutations in this study and previous studies suggested that the truncating variants in the RD cause more severe early‐onset refractory epilepsy, representing a type of variants distinct from loss‐of‐function missense variants in the catalytic domain or gain‐of‐function missense variants in the auto‐inhibitory domain.